2019
DOI: 10.1016/j.bbmt.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Pregnancy-Specific Glycoprotein 1 Has a Protective Role in a Murine Model of Acute Graft-versus-Host Disease

Abstract: Acute graft-versus-host disease (aGVHD) is an immune-mediated reaction that can occur after hematopoietic stem cell transplantation in which donor T cells recognize the host antigens as foreign, destroying host tissues. Establishment of a tolerogenic immune environment while preserving the immune response to infectious agents is required for successful bone marrow transplantation. Pregnancy-specific glycoprotein 1 (PSG1), which is secreted by the human placenta into the maternal circulation throughout pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
5
11
0
1
Order By: Relevance
“…Medical Immunology (Russia)/Meditsinskaya Immunologiya Медицинская Иммунология PSG1 administration significantly reduced weight loss and mortality associated with a GVHD [18]. Interestingly, and consistent with our data, PSG9 induced Treg differentiation in vitro both at the level of human and mouse cells [17].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Medical Immunology (Russia)/Meditsinskaya Immunologiya Медицинская Иммунология PSG1 administration significantly reduced weight loss and mortality associated with a GVHD [18]. Interestingly, and consistent with our data, PSG9 induced Treg differentiation in vitro both at the level of human and mouse cells [17].…”
Section: Discussionsupporting
confidence: 88%
“…We assessed the role of PSG in the regulation of the production of basic cytokines and chemokines by immunocompetent human blood cells without additional inducers under conditions of 18 We found that when introduced into the culture of mononuclear cells, PSG reduced the production of proinflammatory cytokines IL-6, IL-8, IL-17, IFNγ, TNFα [40]. In general, the integral cytokine profile under PSG's action is formed as an anti-inflammatory (Th2).…”
Section: The Role Of Psg In the Regulation Of The Cytokine And Chemokine Profiles Of Immunocompetent Cellsmentioning
confidence: 99%
“…The cell contact-independent mechanism of Tregs is achieved through the secretion of inhibitory cytokines, and TGF-β1 is essential for the proliferation and inhibitory activity of Tregs ( 53 ). The activation of TGF-β1 is necessary to induce the production of CD4 + FOXP3 + Tregs, and Tregs can then secrete TGF-β1 and participate in immune regulation ( 54 , 55 ). Studies have shown that TGF-β1 can promote the differentiation of initial CD4 + T cells into Tregs, and TGF-β1 secreted by Tregs can play a role in maintaining the inhibitory properties of Tregs by binding to its receptors.…”
Section: Tgf-β1 In Fetal-maternal Immune Tolerancementioning
confidence: 99%
“…The case is stronger for a role in immune tolerance of the invading trophoblast, especially in humans where PSGs, acting through TGFβ1, induce proliferation of regulatory T-cells in the uterus ( 46 , 130 ). There is growing evidence for a similar mechanism in rodents ( 140 ) and there could be a link between PSG expression by the endometrial cups of the horse and the presence of regulatory T-cells in their vicinity ( 145 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblast giant cells express Psg22 in the first half of mouse pregnancy, whereas the spongiotrophoblast expresses Psg16 , Psg21 and Psg23 in the second half ( 138 ). Mouse Psg23 can activate latent TGFβ1 ( 139 ) and likely increases the availability of regulatory T-cells, as shown by administering recombinant human PSG1 to mice ( 140 ).…”
Section: Immunosuppressionmentioning
confidence: 99%